TRADE DYNAMICS IN ZIMBABWE (1980-2012): "THE UNTOLD TRADE STORY OF ZIMBABWE" - Talknice Saungweme (Russian Journal of Agricultural and Socio-Economic Sciences, 2013)
Zimbabwe in 1980, when it became independent from British rule, it inherited a developed and predominantly white controlled economy. Since then, the government of Zimbabwe instituted a number of reforms that transformed the economy from being more of socialism to more of capitalism, as it is today (2013). More importantly, is the change in trade dynamics between 1980 and the post 2000 period. National, global and regional trade developments and resultant policies have also contributed to the noted trade shift. The historical decade of economic contraction and political developments, from the start of the new millennium, affected the country's real economy, as was manifested in shrinking production capacity and hence the composition, value, volume and source of both exports and imports.